Ultrasound-Assisted, BF 3·oEt 2-Promoted, Multicomponent Synthesis of Chromene-Based Podophyllotoxin Analogues - Santos, Fernanda A. [UNESP]; Laurentiz, Rosangela S. [UNESP] (Thieme, 2024)
A novel method was developed to synthesise chromene-lactone analogues of podophyllotoxin using an ultrasound-assisted multicomponent reaction (MCR). The MCR involved tetronic acid, phenols, and aromatic aldehydes and was promoted by BF 3 ·OEt 2, resulting in the production of ten derivatives with different substituents on the aromatic rings in yields ranging from 32% to 93%. These compounds are of interest due to their reported activity against tumour cells. Their ease of synthesis through the MCR may allow for more in-depth studies on anticancer activity, as well as investigations of other biological targets. The synthesised derivatives contain important pharmacophoric groups for potential applications in medicinal chemistry.
Keywords: chromenes; heterocyclic compounds; lactones; multicomponent reactions; tetronic acid